(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
Some problematic guidelines immersed in the category of political subjectivity of teachers in the field of human rights education are addressed. The reflection of which runs between the justifications of the ontology of the self and the epistemologically based explanatory efforts of the collective consciousness. Therefore, by means of a theoretical review, the ontological origin of the problem and the way in which some of its comprehension difficulties are weighed in subjectivity as a category are exposed to then demarcate the ways in which it bursts into the recent history of education in Colombia. It is argued that the political subjectivity of the human rights teacher is crossed by the confluence of social forces that come from the field of popular education, the expectations opened by the renewal process of the constitution of 1991 and the reaction in the territories of some sectors of civil society to the intensification of the armed conflict. It is concluded that human rights education in the school environment significantly affects the shaping of the political subjectivity of its protagonists. Teachers tend to increase their potential to establish networks and pedagogical work collectives and to participate in collective actions that go beyond the school environment.